Building Peace Through Knowledge : The Israeli-Palestinian Case - Al-Krenawi, Alean (Springer International Publishing : Imprint: Springer, 2017)
This groundbreaking volume documents a comprehensive peacebuilding initiative in addressing the Israeli-Palestinian conflict and reviews the broad theoretical base underlying these efforts. Theory chapters discuss intrinsic peace-related concepts, including the nature of conflict, elements of individual and group identity, the long-term psychological effects of prolonged political hostilities, and the mechanisms of reconciliation and inclusiveness. Central to the coverage is the ambitious Building Peace through Knowledge Project, a four-year multidisciplinary program featuring a diverse palette of professional and community interventions to reduce the occurrence and trauma of political violence. The author reveals powerful insights connecting knowledge to peacebuilding by analyzing: · The relationships between attitudes and ideology in intergroup conflict. · The psychosocial impact of political violence among Israelis and Palestinians. · The literature on people-to-people interventions (P2Ps) in conflict reduction. · The roles of forgiveness, reconciliation, and fairness in conflict resolution. · The methodology and findings of the Building Peace through Knowledge Project. · The potential of knowledge-based interventions in building sustainable peace in other regions. Practitioners, mental health professionals, and scholars with interests in multicultural mental health, cross-cultural psychology, political violence, and peace education will look to Building Peace through Knowledge as an ideabook, a mission statement, and a road map toward a more stable world. .
Keywords: Social sciences.; Public policy.; Social work.; Cross-cultural psychology.; elektronické knihy; electronic books